The Impact of the Corporate Merger on Financial Efficiency and Governance in PT Perkebunan Nusantara I Regional 4 - Garneta, Linaya Naomi; Khasanah, Putri Dwi Aprilia Nur (Asosiasi Ahli Administrasi Indonesia, 2025)
The decline in financial performance and operational inefficiency within state-owned plantation enterprises in recent years has prompted the Indonesian government, through the Holding Perkebunan Nusantara, to implement a restructuring policy by merging several plantation companies. One of the key structural reforms was the merger of PTPN X and PTPN XI into the SupportingCo sub-holding, which significantly affected organizational arrangements and financial operations in PTPN I Regional 4 as an implementing entity. This study aims to examine the impact of the merger on financial efficiency and financial governance within PTPN I Regional 4. A qualitative descriptive approach was applied, using primary data obtained through in-depth interviews with the Assistant Manager of Finance, selected purposely based on expertise and direct involvement in the post-merger transition. The results reveal that the merger contributed to improvements in financial efficiency, particularly through the harmonization of financial systems into a single integrated platform, SAP HANA, which reduced work duplication, accelerated authorization processes, and enhanced accuracy in financial recording. In the aspect of financial governance, the merger supported the development of a more standardized organizational structure aligned with Good Corporate Governance principles through clearer distribution of responsibilities and strengthened independent oversight. Nevertheless, challenges emerged related to cultural integration and employee adaptation, requiring continuous communication, structured training, and phased implementation strategies. These findings indicate that merger success depends not only on system integration but also on human resource readiness, leadership alignment, and cultural consolidation over time.